2012
DOI: 10.1163/156856111x599580
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Validation of the Invariance of Electrowetting Contact Angle Saturation

Abstract: Basic electrowetting theory predicts that a continued increase in applied voltage will allow contact angle modulation to zero degrees. In practice, the effect of contact angle saturation has always been observed to limit the contact angle modulation, often only down to a contact angle of 60 to 70°. The physical origins of contact angle saturation have not yet been explained successfully and unequivocally. At best, scientists have produced multiple disconnected hypotheses (droplet ejection, charge injection, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
85
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(98 citation statements)
references
References 38 publications
13
85
0
Order By: Relevance
“…Quinn et al [18] also reported asymmetric electrowetting curves in positive DC and implied this deviation was observed only in positive DC due to adsorbed negative ions. Moreover, S. Chevalliot et al [19] compared the electrowetting curves of DC and AC in oil ambient showing they deviate at high voltage and reach different contact-angle saturation. In addition, the performance degradation with 1 kHz AC actuation was in between those of positive and negative DC cases in early cycles.…”
Section: Voltage Typementioning
confidence: 99%
“…Quinn et al [18] also reported asymmetric electrowetting curves in positive DC and implied this deviation was observed only in positive DC due to adsorbed negative ions. Moreover, S. Chevalliot et al [19] compared the electrowetting curves of DC and AC in oil ambient showing they deviate at high voltage and reach different contact-angle saturation. In addition, the performance degradation with 1 kHz AC actuation was in between those of positive and negative DC cases in early cycles.…”
Section: Voltage Typementioning
confidence: 99%
“…It is interesting to note that the value of θ max (65.89°) is between 60 and 70°of the saturated contact angle for electrowetting of conducting droplets. 18 The saturation of contact angle likely is related to the condition determining the field-induced stability of the contact line.…”
Section: F/drmentioning
confidence: 99%
“…The Lippmann-Young equation 1.4 predicts that perfect wetting (i.e., zero contact angle) will be achieved at a finite voltage, however in practice this is unfortunately not true. The contact angle will cease to decrease [38,[40][41][42][43]. Several of the proposed CAS mechanisms may be responsible for anomalous electrowetting behavior at voltages above the contact angle.…”
Section: Electrowettingmentioning
confidence: 99%